PENGARUH MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATERI PEMANASAN GLOBAL DI SEKOLAH SMP SWASTA MUHAMMADIYAH-21 DOLOK BATU NANGGAR - Pratiwi K.R, Kesi; Mustika Piliang, Fenny; Damanik, Risjunardi (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to determine the influence of animated video learning media on student learning outcomes in global warming at Muhammadiyah-21 Dolok Batu Nanggar Private Junior High School. This study used a quantitative approach with a true experimental research method, where independent and dependent variables were tested on samples from the experimental and control groups. This study used a Pre-test Post-test Control Group Design. The total population of 124 seventh-grade students was 124, and 62 students were sampled using cluster random sampling. They were divided into two classes: one control class (VII-C) with 31 students and one experimental class (VII-D) with 31 students. Data analysis techniques used were normality tests, homogeneity tests, simple linear regression tests, mean values, standard deviations, and hypothesis testing. The results of the study showed that the normality test for the control class was 0.351 and the experimental class was 0.708. The homogeneity test showed a significance value of 0.0357. The simple linear regression test for the control class yielded a constant value of 43.066, with a correlation coefficient of 0.118, and for the experimental class a constant value of 39.939, with a correlation coefficient of 0.082. The average posttest score for the control class was 67.10, while for the experimental class it was 93.06. The standard deviation for the control class was 7.613, and for the experimental class it was 5.428. In this research hypothesis test, if t count > t table at a significance level of α = 0.05 and degrees of freedom (df) = 30, then H0 is rejected and Ha is accepted. The hypothesis test calculation yielded t count of 16.263 > t table of 1.69726. Based on the research results and data analysis, there is a significant difference and improvement in student learning outcomes using animated video learning media on global warming in seventh-grade students at Muhammadiyah-21 Private Junior High School, Dolok Batu Nanggar.